Relationship Between Domestic Animals, Environmental and Behavioral Factors, and Under-Five Diarrhea in Sidama Region, Ethiopia: A Matched Case-Control Study - Gorfu Geremew; Argaw Ambelu; Dessalegn Dadi; Alemayehu Haddis (Journal of Epidemiology and Global Health)
Abstract Background In Ethiopia’s Sidama National Regional State, diarrhea remains the second most common cause of illness among children under five, despite a decrease in its mortality rate. However, limited research has been conducted in Ethiopia to identify the causes behind the continuing rise in the prevalence of diarrhea in children associated with exposure to domestic animals. Therefore, this study explores the relationship between domestic animal, environmental, and human behavioral factors and confirmed cases of diarrhea in children under five in the Sidama National Regional State of Ethiopia. Methods We conducted a matched-pairs case-control study involving 306 cases and 306 controls in the Sidama region from September 2022 to February 2023. Cases and controls were identified at healthcare facilities, and interviews and observations were completed at residential homes with children under five. We collected data using the KoboCollect application and analyzed it through conditional logistic regressions. The random forest (RF) method with the classification RF model was used to compare its findings with those of the multivariate conditional regression analysis. The statistical analyses were conducted using R v.4.3.2 software. Results The study indicated that having a caretaker who is a housewife [matched adjusted odds ratio (mAOR) = 3.09, 5% CI (1.09, 8.70)], a mean number of chickens ≥ 5 [mAOR = 5.18, 95% CI (2.70, 9.95)], the absence of soap at handwashing facilities [mAOR = 2.61, 95% CI (1.34, 5.10)], those who travel more than 30 min to fetch water [mAOR = 3.14, 95% CI (1.13, 8.78)], children who are in contact with animal feces [mAOR = 2.44, 95% CI (1.24, 4.82)], and households living with animals [mAOR = 3.28, 95% CI (1.71, 6.30)] showed significant associations with under-five diarrhea. The random forest analysis also identified the first five variables as the main risk factors for diarrhea occurrence among children under-five years of age. Conclusions Risk factors for diarrhea among children under-five include a high number of chickens, cohabitation with animals, prolonged water-fetching times, poor hand hygiene, and caretakers’ occupational status. Animal feces management, improved water access, and hygiene education are critical to reducing under-five diarrheal diseases.